Social capital, type of crime, and social control - Moore, Matthew D. (Crime & delinquency, 2016)
Several studies demonstrate a relationship between social capital and reductions in crime. However, recent research has begun to demonstrate that social capital may affect violent and property crime differently. Moreover, some researchers have suggested that specific aspects of social capital affect crime, while other aspects have little or no effect. This study examines social capital’s effect on the total crime rate, violent crime rate, and property crime rate within U.S. counties. In addition, we group social capital measures as Putnam-type (P-Group), Olson-type (O-Group), and recreation-type (R-Group) parochial controls depending on the type of control it is expected to exert. We find that elements of social capital affect both violent crime and property crime, but affect each in different ways. The type of organization affects whether P-Group, O-Group, and R-Group parochial controls reduce crime.